Verbal Means of Persuasion in English Advertising - Hanna Karpenko (Vasyl Stefanyk Precarpathian National University, 2016)
The article deals with verbal means of persuasion in English advertising. It investigates manipulation tactics and features of persuasion in the English ad. Linguistic and cultural aspects of style formation in English and Ukrainian ads are compared in the article.